Analysis of Perceived Vulnerability Based on the Health Belief Model Theory Toward Exclusive Breastfeeding in Stunting Prevention Efforts - Zahara Syafitri; Nur Alam Fajar; Muhammad Cholil Munadi; Esti Sri Ananingsih; Mulya Virgonita I. Winta (Biomedika, 2024)
Stunting is a major health problem that occurs in children under 5 years of age and prevalent in developing countries for years.  A Toddlers is defined as stunted if the measurement results of the child's body length or height show less than -2 Standard Deviation based on WHO data measurement media. Perception The vulnerability of toddlers suffering from stunting will affect the actions of a mother in making prevention efforts in making prevention efforts. Exclusive breastfeeding is important in the growth and development process that can meet the nutritional needs of children. This study aimed to analyze the perception of vulnerability to exclusive breastfeeding in an effort to prevent stunting. Exclusive breastfeeding in stunting prevention efforts. The research method uses a quantitative research design quantitative research design with a cross sectional approach, the sample studied was as many as 154 mothers of toddlers 6-36 months with purposive sampling technique. Data analysis using Chi-Square test and Logistic Regression Test. The results showed that the independent variables of maternal knowledge and attitude had a significant relationship to the dependent variable of exclusive breastfeeding in an effort to prevent stunting with a p-value of 0.001 and 0.005 (p-value<0.005).  The results of multivariate analysis showed that maternal knowledge and attitude were the dominant factors of perception of maternal vulnerability in exclusive breastfeeding in an effort to prevent stunting (p value <0.000). It can be concluded that maternal knowledge and attitudes have a significant relationship with the action of exclusive breastfeeding in preventing stunting in an effort to prevent stunting.